4.2 Woods -Quality Control Procedures at Gold Fields Ghana Limited, Tarkwa Mine - Reginald N. Boryor; Steven D. Woods (The Southern African Institute of Mining and Metallurgy, 2005)
1.0 Introduction ?Low grade, high tonnage, open pit gold mine. ?Gold bearing Tarkwaian conglomerates. ?Reverse Circulation percussion drilling (25m X 25m grid). ?Composite 1m intervals, logged and split in the field to provide±2Kg samples. ?Samples used to build grade control block models using SURPAC. ?Approximately 100,000-130,000 meters drilled per year. ?RC samples are assayed using Rapid Cyanide Leach (RCL). ?Check assays are done using Fire Assay